Antenatal Depression and Anxiety Among Women with Threatened Abortion: A Case-Control Study - Bahar Sariibrahim Astepe; Sukriye Bosgelmez (Gynecology Obstetrics & Reproductive Medicine)
Objective: Threatened abortion is a stressful condition for a pregnant woman which may influence mental health. This study aims to investigate the relationship between threatened abortion, anxiety, and depression during pregnancy.